Predictors of patient-reported quality of care in low- and middle-income countries: a four-country survey of person-centered care. (28th July 2021) - Kim, June-Ho; Bell, Griffith A; Ratcliffe, Hannah L; Moncada, Leah; Lipsitz, Stuart; Hirschhorn, Lisa R; Bitton, Asaf; Schwarz, Dan
Abstract: Background: Person-centeredness is a foundation of high-quality health systems but is poorly measured in low- and middle-income countries (LMICs). We piloted an online survey of four LMICs to identify the prevalence and correlates of excellent patient-reported quality of care (QOC). Objective: The aims of this study were to investigate the examine people's overall ratings of care quality in relation to their experiences seeking care in their respective health systems as well as individual-, provider- and facility-level predictors. Methods: We administered a cross-sectional online survey using Random Domain Intercept Technology to collect a sample of random internet users across India, Kenya, Mexico and Nigeria in November 2016. The primary outcome was patient-reported QOC. Covariates included age, gender, level of education, urban/rural residence, person for whom care was sought, type of provider seen, public or private sector status of the health facility and type of facility. The exposure was an index of health system responsiveness based on a framework from the World Health Organization. We used descriptive statistics to determine the prevalence of excellent patient-reported QOC and multivariable Poisson regression to calculate adjusted prevalence ratios (aPRs) for predictors of excellent patient-reported quality. Results: Fourteen thousand and eight people completed the survey (22.6% completion rate). Survey respondents tended to be young, male, well-educated and urban-dwelling, reflective of the demographic of the internet-using population. Four thousand one and ninety-one (29.9%) respondents sought care in the prior 6 months. Of those, 21.8% rated their QOC as excellent. The highest proportion of respondents gave the top rating for wait time (44.6%), while the lowest proportion gave the top rating for facility cleanliness (21.7%). In an adjusted analysis, people who experienced the highest level of health system responsiveness were significantly more likely to report excellent QOC compared to those who did not (aPR 8.61, 95% confidence interval [95% CI]: 7.50, 9.89). In the adjusted model, urban-dwelling individuals were less likely to report excellent quality compared to rural-dwelling individuals (aPR 0.88, 95% CI: 0.78, 0.99). People who saw community health workers (aPR 1.37, 95% CI: 1.12, 1.67) and specialists (aPR 1.30, 95% CI: 1.12, 1.50) were more likely to report excellent quality than those who saw primary care providers. High perceived respect from the provider or staff was most highly associated with excellent ratings of quality, while ratings of wait time corresponded the least. Conclusion: Patient-reported QOC is low in four LMICs, even among a well-educated, young population of internet users. Better health system responsiveness may be associated with better ratings of care quality. Improving person-centered care will be an important component of building high-quality health systems in these LMICs.